The Impact of Media Hype in Shaping Public Opinion: Al-Hadath Channel's Coverage of Israel's Strikes on Iran-A Survey Study of the Dhi Qar Governorate Audience - Ethar Khudhur Abdulhusein (Genius Journals, 2025)
The study aims to identify the impact of media hype in shaping public opinion regarding Al-Hadath Channel's coverage of Israel's strikes on Iran. It also aims to measure the extent of the impact of media hype on the attitudes and opinions of the Dhi Qar Governorate audience. It also aims to assess the public's awareness of the dangers of media exaggeration and its impact on their perceptions. It also aims to study the relationship between demographic variables (such as age, gender, and educational level) and the extent of influence of media coverage. The researcher relied on a quantitative survey approach on a random sample of (431) male and female respondents from Dhi Qar Governorate. The researcher reached the following conclusions: The study results showed that the media hype practiced by Al-Hadath Channel in its coverage of the Israeli strikes against Iran had a direct impact on shaping the attitudes and opinions of the public in Dhi Qar Governorate. The excessive repetition of violent images, exaggerated analysis, and the use of sensational headlines have led to exaggerated perceptions of the magnitude and impact of the attacks, heightening feelings of fear and anxiety among a large segment of the public. The study revealed a relative lack of awareness of the dangers of media hype, particularly among the less educated and younger groups, making them more vulnerable to negative media discourse. Women, youth, and those with a medium or low level of education were found to be more affected by media hype than other groups, indicating disparities in critical and analytical abilities among audience segments.
Keywords: Media hype; public opinion; Al-Hadath TV; Israel